A letter to a student (Journal of Parents and Teachers, 2023)
This article is a letter that reflects the first experience of a teacher with a gifted student (the letter is for this student). It also discusses the current situation of gifted students and the challenges that they are facing.
Keywords: Parents; Gifted Students; Education system